Knowledge acquisition and model abstraction using soft systems methodology / Nadiah Atikah Abdullah - Abdullah, Nadiah Atikah (2011)
Knowledge Acquisition and Model Abstraction Using Soft Systems Methodology (SSM) is a thesis project of the application of SSM as an inquiry approach in order to understand the problem situation which support the decision on organizational change that attempt to align their business process with Information System (IS) development. The competitive environment has urged the organization to engage in automating their business from current manual system. The interest lies on Soft Systems Methodology which is concerned about the aspect of the organization as well as the system itself. The project covers four areas of studies which are Knowledge Acquisition, Model Abstraction, Soft Systems Methodology and design in order for the proposed project to produce the expected deliverables. The aim is to apply Soft Systems Methodology as an inquiry approach to the problem situation. The objectives of the project are; to analyze the current business problem situation, graphically described the problem situation, and proposed a conceptual model based on root definition. Soft Systems Methodology is used as problem structuring approach that contributes in designing Conceptual Model as a tool that focused on improvements to organizational problems as well as the Knowledge Acquisition which allow the process of acquiring knowledge in order to seize the overall situation explicitly and Model Abstraction for the process of model conceptualization. The project follows several stages which consist of the Preliminary Study phase, Data Gathering Phase, Data Analysis phase and Design phase. All the phases are conducted in depth in order to achieve the objectives of the proposed project. Conceptual Design concentrates on idealizing the core activities and meets the stakeholder needs. Bedsides, this project delivers a Conceptual Model that provides an understanding towards the problem situation and support the organization transformation decision.